Turning pages, crossing cultures: libraries as gateways to edu-tourism - Ahmad Tarmizi, Wan Ainol Mursyida; Azmi, Nor Azlina; Mohd Ridwan, Noor Syakinah (Universiti Teknologi MARA, Kedah, 2025)
For the travellers that venturing into uncharted places, it is their curiosity that leads the way. Imagine they are stepping into a space where culture, history, and knowledge meet, where learning transcends textbooks and tourist guides, and where your surroundings themselves tell stories of a region’s past, present, and future. This is the allure of edu-tourism, which is a unique form of travel that intertwines exploration with education. Defined simply, edutourism (educational tourism) is travel centred around learning. It is a journey to places with the intent of gaining knowledge, whether through structured programs or immersion in historical, cultural, or environmental aspects of a destination. The authors as information professionals always look at a library that UNESCO defines as an organization, or part of an organization, whose main goals are to build and maintain a collection and to facilitate the use of such information resources and facilities as are required to meet the informational, research, educational, cultural, or recreational needs of its users, as a pivotal site for edu-tourism. This article delves into libraries' significance as locations for inspiration, education, and cultural exchange and therefore can enhance knowledge sharing globally. We can see how libraries, such as the beautiful Starfield Library in Seoul, South Korea, and other monuments in China and Japan, are influencing the landscape of edu-tourism.